CACN Chair's Select Abstract Presentations: CACN 2015 President's Prize Lidocaine for status epilepticus in pediatrics. (3rd June 2015) - Zeiler, FA; Zeiler, KJ; Teitelbaum, J; Gillman, LM; West, M; Kazina, CJ
Abstract : Introduction: Our goal was to perform a systematic review of the literature on the use of intravenous lidocaine in pediatrics for status epilepticus (SE) and refractory status epilepticus (RSE) to determine its impact on seizure control. M ethods: All articles from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to November 2014), and gray literature were searched. The strength of evidence was adjudicated using both the Oxford and GRADE methodology by two independent reviewers. Results: Overall, 20 original studies were identified, with 19 manuscripts and 1 meeting abstracts. Two hundred and thirty-five pediatric patients were treated for 252 episodes of SE/RSE. Patients had varying numbers of anti-epileptic drugs (AEDs), 2 to 8, on board prior to lidocaine therapy. During 20 of the 252 (7.9%) episodes of SE/RSE, phenytoin was on board. The dose regimen of lidocaine varied, with some utilizing bolus dosing alone; others utilizing a combination of bolus and infusion therapy. Overall, 60.0% of seizures responded to lidocaine, with complete cessation and greater than 50% reduction seen in 57.6% and 12.3% respectively. Patient outcomes were sparingly reported. Conclusions: There currently exists level 2b, GRADE C evidence to support the consideration of lidocaine for SE and RSE in the pediatric population.